Leisure-Time Physical Activity and Characteristics of Social Network Support for Exercise Among Latinas. Issue 2 (February 2018) - Soto, Sandra H.; Arredondo, Elva M.; Haughton, Jessica; Shakya, Holly
Purpose: To examine the association between characteristics of social support for exercise and moderate-to-vigorous leisure-time physical activity (LTPA) among Latinas. Design: This cross-sectional study used baseline data from a cluster randomized controlled trial. Setting: The study was conducted in 16 churches located in San Diego County. Participants: Participants (N = 436) were Latinas between 18 and 65 years old who did not self-report >150 minutes or did not exceed 250 minutes of moderate-to-vigorous PA per week measured by accelerometer. Measures: Latinas listed up to 6 individuals who had provided support for exercise within the past 6 months, including their gender, relationship with the respondent, types of support provided, and respondent's satisfaction with support. Self-reported LTPA was dichotomized (none vs any). Analyses: We generated dyads between Latinas who named ≥1 supporter (n = 323) and each supporter they named (n = 569 dyads). Logistic regression analyses were conducted using generalized estimating equations to adjust for multiple observations per participant. Results: Having an exercise partner (odds ratio [OR]: 2.16; 95% confidence interval [CI]: 1.01-4.62), help with household duties (OR: 2.70; 95% CI: 1.35-3.38), being "very much" satisfied with support (OR: 2.33; 95% CI: 1.26-4.30), and naming >2 supporters (OR: 2.57; 95% CI: 1.06-6.25) was positively associated with LTPA. Conclusions: Findings suggest specific aspects of support for exercise that should be targeted in future interventions to promote LTPA.